Forest Mole – An Audio-Based VR Game - Exploring spatial audio-simulation for navigation and spatial awareness in games - Altenstedt, Ida; Willig, Rebecka (My University, 2026)
This thesis follows the design and implementation of an audio-based VR game. The game was created as part of a process using the Research Through Design method, in order to answer the research question: What are important aspects to consider when designing audio games for VR? The answer is precented in the form of a SWOT analysis, containing 25 observations spanning four categories. The report contains the first two development cycles for the audio-based VR game Forest Mole. During development, various issues arose, the most important one being related to the functionality of the spatial audio library used. While this negatively affected the expectation of the given result, it offered insight into broader aspects of the current state of audio development in games. This in turn affected the observations found for the SWOT analysis.
Keywords: computer science, project, thesis, SWOT analysis, VR, 3D audio, games, audio games, sound design, spatial audio